Factors Determining the Success of an Interpreter and His Performance - kambiz mahmudzadeh (Matn/Pizhūhī-i Adabī, 2002)
A close study of the conduct of a translator or an interpreter indicates that there are a large number of factors which can play a significant role in their success or failure in their profession. The present paper is intended to probe into a number of these factors which appear to have a rather more important role in the profession of interpreters. It is accepted though, by the majority of the scholars, if not all, that these two disciplines namely interpreting and translating are so highly Interwoven that what applies to one necessarily applies to the other as well, perhaps to a more or less degree. For this reason, since it is beyond the scope of the present paper, translating will not be focused upon unless prescribed by the discussion. Attempt has also been made to illustrate the features of each of these factors as well as their impact on the performance of the interpreters. Finally, whenever necessary, some solutions to the problems are provided at each stage.